2011
DOI: 10.1111/j.1743-6109.2011.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxious and Avoidant Attachment, Vibrator Use, Anal Sex, and Impaired Vaginal Orgasm

Abstract: Introduction Disturbances in intimate relationships are among the risk factors for female sexual dysfunction. Insecure styles of anxious attachment (preoccupations about abandonment) and avoidant attachment (avoidance of closeness in relationships) are robustly associated with sexual problems, relationship difficulties, and several indices of poorer physical and mental health. Similar indices of poorer sexual, relationship, and health functioning are associated with impairment of orgasm trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
42
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 45 publications
14
42
2
1
Order By: Relevance
“…Brassard et al (2007) also found that only attachment avoidance was associated with more sexual problems in men, and that this association held only when the women also presented avoidance. On the other hand, our results did not replicate previous findings showing that attachment anxiety was associated with lower sexual functioning and impaired orgasmic response in women (Birnbaum, 2007;Costa & Brody, 2011). This divergence might be explained by the fact that our sample was comprised of women who present with a vulvo-vaginal pain problem known to affect all aspects of sexual function, often to clinical levels (Desrochers et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Brassard et al (2007) also found that only attachment avoidance was associated with more sexual problems in men, and that this association held only when the women also presented avoidance. On the other hand, our results did not replicate previous findings showing that attachment anxiety was associated with lower sexual functioning and impaired orgasmic response in women (Birnbaum, 2007;Costa & Brody, 2011). This divergence might be explained by the fact that our sample was comprised of women who present with a vulvo-vaginal pain problem known to affect all aspects of sexual function, often to clinical levels (Desrochers et al, 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…However, in a long-term perspective, these non-assertive behaviors may have detrimental effects on pain, sexual functioning and satisfaction. Correlational studies already show that attachment anxiety is associated with poorer sexual experiences (Birnbaum, 2007;Brassard, Peloquin, Dupuy, Wright, & Shaver, 2012;Butzer & Campbell, 2008;Costa & Brody, 2011;Davis et al, 2006;Gentzler & Kerns, 2004) and greater sex-related worries (Birnbaum et al, 2006;Davis et al, 2006). Two studies using a dyadic approach have shown interesting partner effects indicating that an individual's attachment can predict their partner's sexual outcome (Brassard et al, 2012;Butzer & Campbell, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Greater masturbation frequency is also associated with more dissatisfaction with relationships and less love for partners (Brody, 2010;Brody & Costa, 2009). In contrast, PVI is very consistently related to better health (Brody, 2010;Brody & Costa, 2009;Brody & Weiss, 2011;Costa & Brody, 2011, 2012, better sexual function (Brody & Costa, 2009;Brody & Weiss, 2011;Nutter & Condron, 1983, 1985Weiss & Brody, 2009), and better intimate relationship quality (Brody, 2010;Brody & Costa, 2009;Brody & Weiss, 2011).…”
mentioning
confidence: 91%
“…It is difficult to reconcile the view that masturbation improves mood with the findings in both sexes that greater masturbation frequency is associated with more depressive symptoms (Cyranowski et al, 2004;Frohlich & Meston, 2002;Husted & Edwards, 1976), less happiness (Das, 2007), and several other indicators of poorer physical and mental health, which include anxious attachment (Costa & Brody, 2011), immature psychological defense mechanisms, greater blood pressure reactivity to stress, and dissatisfaction with one 0 s mental health and life in general (for a review, see Brody, 2010). It is equally difficult to see how masturbation develops sexual interests, when greater masturbation frequency is so often associated with impaired sexual function in men (Brody & Costa, 2009;Das, Parish, & Laumann, 2009;Gerressu, Mercer, Graham, Wellings, & Johnson, 2008;Lau, Wang, Cheng, & Yang, 2005;Nutter & Condron, 1985) and women (Brody & Costa, 2009;Das et al, 2009;Gerressu et al, 2008;Lau, Cheng, Wang, & Yang, 2006;Shaeer, Shaeer, & Shaeer, 2012;Weiss & Brody, 2009).…”
mentioning
confidence: 97%
See 1 more Smart Citation